Higher education : demand and response : the Quail Roost seminar of December 1968 - Niblett, William R. (San Francisco, California : Jossey-Bass Inc., Publishers, 1970)
he Seminar whose proceedings are recorded in this book was concerned with some of the fundamental, and therefore continuing, problems of higher education. Many conferences on higher education concentrate upon a particular area of practical concern - upon university organization and ad-ministration, for example, decision-making, student development, the causes of student drop-out, curriculum design, problems of costing, etc. This one was at bottom philosophical in its interests; concerned with presuppositions often taken for granted in higher education in our time, with why? questions as well as with questions of what? and how? and apt to inquire how relevant some of our present objectives and practices really are.
Chapter 1. A head-but in what Direction? -- Chapter 2. The Contribution of Higher Education to the Life of Society -- Chapter 3. The University and Personal Life: Student Anarchism and the Educational Contract -- Chapter 4. The European University from Medieval Times -- Chapter 5. Development of Higher Education in the United Kingdom -- Chapter 6. Institutions of Higher Education in the USA -- Chapter 7. Institutions of Higher Education in Canada -- Chapter 8. University Initiative in Response to Change -- Chapter 9. Elite and Popular Functions in American Higher Education -- Chapter10. Higher Education and Personal Life: Changing Attitudes -- Chapter 11. Insight and Foresight in Higher Education.
Includes bibliographical references and index.
Keywords: EDUCATION